Prognostic significance of IDH-1 and MGMT in patients with glioblastoma: one step forward, and one step back? - Combs, Stephanie; Rieken, Stefan; Wick, Wolfgang; Abdollahi, Amir; Deimling, Andreas von; Debus, Jürgen; Hartmann, Christian (Radiation oncology, 2011)
A group of 160 patients with primary glioblastoma treated with radiotherapy and temozolomide was analyzed for the impact of O6-methly-guanly-methyl-transferase (MGMT)-promoter methylation as well as isocitrate dehydrogenase (IDH)1-mutational status. Unexpectedly, overall survival or progression-free survival were not longer in the group with methylated MGMT-promoter as compared to patients without that methylation. IDH-1 mutations were significantly associated with increased overall survival.
Gesehen am 14.04.2022